HIV seropositivity and Neoplasms with plasma cell morphology: Plasmablastic lymphoma and Plasma cell myeloma : Is it a chance association or an increasing occurrence? - Gupta, Anupama Praveen; Kumbhalkar, Dinkar T; Parate, Sanjay Nanaji; Kawthalkar, Shirish M; Nayak, Suprita; Kodate, Purnima M; Shende, Nitin; Hake, Ganesh (Annals of Pathology and Laboratory Medicine, 2015)
Plasma cell tumors have shown an increased incidence in Human Immuno Deficiency Virus (HIV) positive patients. Plasma cell tumors in these patients occur in a younger age group than that in the general population, present at unusual sites and progress rapidly to involve multiple sites, including the soft tissues and viscera. Pathologically, many of these tumors show plasmablastic morphology. We present here six interesting cases of plasma cell tumor in HIV seropositive patients diagnosed on fine needle aspiration cytology (FNAC) and confirmed on histopathology and immunohistochemistry. These lesions presented at unusual locations like subcutaneous, oral and nasal. They presented at younger age, had aggressive behavior and unusual cytomorphology.